العلاقة بين فاعلية هيكل الرقابة الداخلية وقابلية القوائم المالية للمقارنة في ظل الأثر المعدل لخصائص مجلس الإدارة: دراسة تطبيقية علي الشركات المقيدة بالبورصة المصرية - موسى، بوسي حمدي حسن Mousa, Bousi Hamdi Hasan (جامعة الإسكندرية - كلية التجارة - قسم المحاسبة والمراجعة, 2023)
استهدف البحث دراسة واختبار أثر فاعلية هيكل الرقابة الداخلية على قابلية القوائم المالية للمقارنة، وكذلك اختبار أثر بعض خصائص مجلس الإدارة على هذه العلاقة. ولتحقيق هدف البحث تم تحليل الدراسات المحاسبية السابقة لاشتقاق فرض البحث. ثم تم إجراء دراسة تطبيقية على عينة مكونة من الشركات المقيدة بالبورصة المصرية خلال الفترة من 2019-2021. وخلص البحث إلى وجود تأثير إيجابي ولكنه غير معنوي لفاعلية هيكل الرقابة الداخلية على قابلية القوائم المالية للمقارنة، كذلك وجود تأثير إيجابي ومعنوي للخبرة المالية والمحاسبية لأعضاء مجلس الإدارة على العلاقة بين فاعلية هيكل الرقابة الداخلية وقابلية القوائم المالية للمقارنة. بينما لا يوجد تأثير معنوي سواء لوجود أعضاء مؤسسين في مجلس الإدارة أو الارتباطات السياسية لأعضاء مجلس الإدارة على العلاقة بين فاعلية هيكل الرقابة الداخلية وقابلية القوائم المالية للمقارنة. The research aimed to study and test the impact of the effectiveness of the internal control structure on the financial statements comparability, as well as to test the impact of some of the characteristics of the board of directors on this relationship. To achieve the aim of the research, the previous accounting studies were analyzed to derive the research hypothesis. Then, an applied study was conducted on a sample of companies listed on the Egyptian Stock Exchange during the period from 2019-2021. The research concluded that there is a positive but not significant effect of the effectiveness of the internal control structure on the financial statements comparability, as well as there is a positive and significant effect of the financial and accounting experience of the members of the Board of Directors on the relationship between the effectiveness of the internal control structure and the financial statements comparability. While there is no significant effect for either the presence of founding members in the Board of Directors or the political connections of the members of the Board of Directors, on the relationship between the effectiveness of the internal control structure and the financial statements comparability.
Keywords: القوائم المالية -- الشركات الاقتصادية -- البورصة المصرية